Estimation of postmortem interval using vitreous potassium levels in cases of fatal road traffic collision - Suzanne N. Foster; Paul R. Smith; Michael Biggs; Guy N. Rutty; Frances E. Hollingbury; Stephen R. Morley (Archives of Forensic Medicine and Criminology, 2016)
Aim of the study : To produce a formula that can accurately predict postmortem interval (PMI) based on vitreous potassium levels using road traffic collision fatalities. Material and methods: Vitreous humour samples were taken from 78 individuals who had died following road traffic collisions between 2010 and 2015. Samples were obtained from both eyes and were sent for on-site analysis. Measurement of potassium was by an indirect ion-specific electrode Siemens diagnostics ADVIA 2400 chemistry system. Exact time of death was known from police reports, the time of postmortem was recorded and the postmortem interval was calculated. Linear regression was then used to analyse the relationship between the two. The impact of age was also assessed. Results: PMI was between 6 and 162 hours. As vitreous potassium increases, the PMI also increases; exhibiting a linear relationship. This is illustrated by a regression equation of PMI = 6.42[K+] – 40.94, R = 0.67 (p < 0.001). This produced a formula closely comparable with three other studies proposed in previous literature and produces estimates that may exceed one calendar day. When both age and medical intervention are accounted for there is an insignificant improvement in prediction. Conclusions : Validated methods have been used to produce a formula for prediction of PMI using vitreous potassium. Although this is specific to road traffic collisions, the methods are transferable and can be seen to be comparable with other recently published methods. Nonetheless, if greater levels of accuracy are required it is suggested that biomarkers delivering a higher level of precision should still be sought.